2017
DOI: 10.1007/s00417-017-3622-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of pseudodrusen subtypes in advanced age-related macular degeneration

Abstract: Among eyes with advanced AMD associated with pseudodrusen, ribbon-dominant type pseudodrusen were more prevalent in eyes with GA or RAP and were associated with large soft drusen and female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Genomic DNA was extracted from peripheral blood samples and purified using a Puregene DNA Isolation Kit (Gentra Systems, Minneapolis, MN, USA). Genotyping was performed using TaqMan genotyping assays with a 7300/7500 Real-Time PCR System (Applied Biosystems, Foster City, CA, USA) in accordance with the manufacturer’s recommendations, as recently described 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood samples and purified using a Puregene DNA Isolation Kit (Gentra Systems, Minneapolis, MN, USA). Genotyping was performed using TaqMan genotyping assays with a 7300/7500 Real-Time PCR System (Applied Biosystems, Foster City, CA, USA) in accordance with the manufacturer’s recommendations, as recently described 37 .…”
Section: Methodsmentioning
confidence: 99%
“… 67 It was found that the prevalence of GA was associated with the presence of ribbon-dominant (confluent)-type pseudodrusen, large soft drusen, and female gender. 68 Pigmentary disturbances are a frequent finding in AMD that can be in the form of either focal hyperpigmentation or hypopigmentation. Progressive well-demarcated atrophic patches of the RPE may appear in the perifoveal area.…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%
“…If an exudative change was observed on OCT, FA/ICGA was performed to confirm the MNV subtype. The presence of reticular pseudodrusen was defined as the presence of characteristic imaging by at least one imaging modality, as previously described 24 . Because this study is a multi-institutional study, the case discrimination and measurement of the retinal and choroidal structure were performed by 3 retinal specialists (Y.S, K.T, A.M) in each institute, not setting a reading center.…”
Section: Methodsmentioning
confidence: 99%